Detection of SARS-CoV-2 RNA in selected agricultural and food retail environments in Tehran, Iran - Rafieepoor, Maedeh; Mohebbi, Seyed Reza; Hosseini, Seyed Masoud; Tanhaei, Mohammad; Saeedi Niasar, Mahsa; Kazemian, Shabnam; Asadzadeh Aghdaei, Hamid; Moore, Matthew D.; Zali, Mohammad Reza (Frontiers in Public Health, 2022)
The SARS-CoV-2 pandemic has and continues to impose a considerable public health burden. Although not likely foodborne, SARS-CoV-2 transmission has been well documented in agricultural and food retail environments in several countries, with transmission primarily thought to be worker-to-worker or through environmental high touch surfaces. However, the prevalence and degree to which SARS-CoV-2 occurs in such settings in Iran has not been well documented. Furthermore, since SARS-CoV-2 has been observed to be shed in the feces of some infected individuals, wastewater has been utilized as a means of surveilling the occurrence of SARS-CoV-2 in some regions. This study aimed to investigate the presence of SARS-CoV-2 RNA along the food production and retail chain, from wastewater to water used for irrigation, to harvested and marketed vegetables. From September 2020 to January 2021, vegetables from agricultural areas of Tehran province (n=35), their irrigated agricultural water (n=8), treated wastewater mixed into irrigated agricultural water (n=8), and vegetables collected from markets in Tehran (n=72) were collected to investigate the presence of SARS-CoV-2 RNA. The vegetable samples were washed with TGBE buffer and concentrated with 6000 polyethylene glycol, while water samples were concentrated by an adsorption-elution method using an electronegative filter. RT-qPCR targeting the SARS-CoV-2 N and RdRp genes was then conducted. SARS-CoV-2 RNA was detected in 51/123 (41.5%) of the samples overall. The presence of SARS-COV-2 RNA in treated wastewater, irrigation water, field vegetables, and market produce were 75%, 37.5%, 42.85% and 37.5%, respectively. These results indicate that SARS-CoV-2 is present in food retail and may also suggest that produce can additionally be contaminated with SARS-CoV-2 by agricultural water. This study demonstrates that while SARS-CoV-2 RNA was detected on foods which are minimally washed out and eaten raw there is no evidence that there is a public health risk in consuming these kinds of foods.